2020
DOI: 10.3390/ijms21165735
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of 1,3,4-Thiadiazole-Derived Ligands and Their Zn(II) and Cu(II) Complexes Which Demonstrate Synergistic Antibacterial Effects with Kanamycin

Abstract: Classical synthetic protocols were applied for the isolation of three novel 1,3,4-thiadiazole derivatives which were then complexed with the biologically important Cu(II) and Zn(II) ions. All free ligands and their corresponding complexes were characterized using a number of spectroscopic techniques including Ultraviolet-visible (UV–vis), Fluorescence, Infrared (FT-IR), tandem liquid chromatography-mass (LC-MS), X-ray diffraction (XRD), and Nuclear Magnetic Resonance (NMR) spectroscopy (1H, 13C, HSQC, HMBC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
10
26
0
Order By: Relevance
“…These results are consistent with the IR spectra (Section 2.2), which suggest the presence of additional water molecules. Moreover, in the context of the ligand:metal ratio, there is a similarity between Cu(II) complexes 6-9 and those previously reported by our group [20,29], which support the hypothesis that the Cu(II) complexes 6-9 consist of two coumarin-thiadiazole hybrid ligands bound to one central Cu(II) ion with the coordination bonds formed via lone pairs of electrons coming from the deprotonated phenolic group and the nearest (in space) thiadiazole nitrogen. Additionally, the coordination sphere is filled most likely with four water molecules, which in turn enables the variety of coordination numbers (from 4 up to 8).…”
Section: Microanalysis (C H N and S) And Atomic Absorption Spectroscopy (Aas)supporting
confidence: 85%
See 1 more Smart Citation
“…These results are consistent with the IR spectra (Section 2.2), which suggest the presence of additional water molecules. Moreover, in the context of the ligand:metal ratio, there is a similarity between Cu(II) complexes 6-9 and those previously reported by our group [20,29], which support the hypothesis that the Cu(II) complexes 6-9 consist of two coumarin-thiadiazole hybrid ligands bound to one central Cu(II) ion with the coordination bonds formed via lone pairs of electrons coming from the deprotonated phenolic group and the nearest (in space) thiadiazole nitrogen. Additionally, the coordination sphere is filled most likely with four water molecules, which in turn enables the variety of coordination numbers (from 4 up to 8).…”
Section: Microanalysis (C H N and S) And Atomic Absorption Spectroscopy (Aas)supporting
confidence: 85%
“…In the case of Zn(II) complexes, the lactone band is notably broader, most likely due to the overlap with the C=O stretching band of the acetate, except in complex 12 (Supplementary Figure S2), in which the lactone C=O band remains unaffected. related to the formation of coordination bonds are present between 550-450 cm −1 [27,29]. As expected, the complex formation either does not affect the positioning of the lactone C=O band or only the slight shifts are observed.…”
Section: Ir(atr) Spectroscopysupporting
confidence: 75%
“…A second manner to associate metal complexes with antimicrobials is to exploit existing antimicrobial compounds as ligands for metal cations. Indeed, as shown in a lot of the previous examples [32,72,73,77,78,80,84,86,87,97,175,176], the metal complexes displayed higher activity than their ligands or their building-blocks themselves. It is therefore suggested that metal-antibiotic combinations could lead to synergistic effects in terms of their respective antimicrobial properties.…”
Section: Synergy Of Metal Complexes With Antimicrobialsmentioning
confidence: 74%
“…This is better than the ligand alone (2.39 mM and 4.78 mM), but much higher than current antibacterials like kanamycin, which demonstrates MICs of 8.05 and 16.10 µ M with respect to the two bacterial strains. Only one of these two zinc complexes was tested together with kanamycin against S. aureus; this induced the fall of their respective MICs, which became 0.34 mM for the thiadiazole-zinc complex, and 1.03 µ M for the kanamycin [78]. Thus, rather than perform antimicrobial assays directly on new compounds, it is sometimes interesting to use them as cofactors of known antibiotics to determine their synergistic effects.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation